Improvement of understanding of physics concepts in straight motion materials after the application of the Discovery Learning model - Fahrunnisa; Pertiwi (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2026)
This study aims to analyze the improvement of students' understanding of physics concepts in straight motion materials after the application of the discovery learning model. The research uses a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 34 students of class X at one of the public high schools in Makassar City who were selected through purposive sampling. Data was collected using a two-tier concept understanding test of 20 items that had been validated and had a KR-20 reliability of 0,82. Learning is carried out through the stages of stimulation, problem statement, data collection, data processing, verification, and generalization. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, paired sample t-test, Cohen's dz, and normalized gain (N-gain). The results showed that the average score increased from 52,35 in the pretest to 78,65 in the posttest. The paired sample t-test showed a significant difference between the pretest and posttest scores, t (33) = 12,94, p < 0,001, with an average N-gain of 0,55 (medium category). These findings show that the application of the discovery learning model is able to improve students' understanding of physics concepts in straight motion materials.